Tinjauan Kesiapan Pemerintah Desa dalam Implementasi Peraturan Menteri Dalam Negeri Nomor 113 Tahun 2014 Tentang Pengelolaan Keuangan Desa (Studi Kasus Pada Pemerintah Desa di Kabupaten Ogan Ilir) - Ika Sasti Ferina; Burhanuddin .; Herman Lubis (JURNAL MANAJEMEN DAN BISNIS SRIWIJAYA, 2016)
The research aimed to assess the readiness of the village Government in Ogan Ilir Regency in the implementation of the Regulation of the Minister of State Number 113 year 2014 concerning the management village financial and assess the constraints and the acceleration strategy in the application. The village government readiness is indicated with four parameter; human resources, organizational commitment, infrastructure and information systems. Type of this research is descriptive qualitative research. The sample used in this study amounted to 92 peoples from village government in Ogan Ilir Regency were selected through purposive sampling method. Methods of data collecting is using primer data from interview and secondary data from library research and documentation. Methods of data analysis using descriptive analysis. The result of this research showed that village Government in Ogan Ilir Regency indicated by the organizational commitment is ready, while the parameters of the human resource, infrastructure and information systems is not ready. Constraints in the implementation is the human resource quality is still not enough, the lack of training, information and communication that run not integrated between the regency and village government, and then the lack of supporting infrastructure. Acceleration strategy in the implementation include the preparation of technical manual book, human resource development through technical guidance and training, preparation of clear information system between the regency and village government and the provision of infrastructure to support the management village financial